Casting method of large-size aluminum alloy
By adopting refining treatment, online degassing, ultrasonic modification treatment and thermal improvement treatment in the aluminum alloy casting process, the problems of hot cracks, mechanical property coordination and poor acid and alkali resistance stability in aluminum alloy casting are solved, and high-quality Quality large size aluminum alloy casting.
Patent Information
- Application Number
- CN202411496424.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
AI Technical Summary
The existing aluminum alloy casting technology is prone to thermal cracks, the mechanical strength and fracture performance are difficult to coordinate, and the acid and alkali resistance are poor, which affects the product yield and use efficiency.
The large -sized aluminum alloy casting method is adopted, including the complete melting, refining treatment, online qi, filtration, casting type, ultrasonic modification treatment, and thermal reform of aluminum alloy ingots. Use potassium chloride, lithium chloride, oxide and refined modifiers in the refining treatment. Add Albe5 intermediate alloys to online qi, and use nano -pour soil liquid and hydroxylhhexylsite and other materials during ultrasound modification treatment. Finally, Perform thermal reform.
Effectively reduce the occurrence of thermal cracks, coordinate and improve the mechanical strength and fracture performance of aluminum alloy, and significantly improve the product's acid -base stability, improve the rate of finished product and use efficiency.
Smart Images

Figure BDA0005101365070000121 
Figure BDA0005101365070000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy casting, and in particular to a casting method of a large-size aluminum alloy. Background Art
[0002] At present, the main production method of aluminum alloy ingots is the ordinary continuous casting method (Direct Chill Casting - DC method). The solidification of liquid metal in the DC method relies on heat transfer from the crystallizer wall and cooling in the secondary cooling water zone. Due to the casting process, the solidification speed of each part is different during the ingot casting process, which in turn generates stress. This stress will tear the ingot during the solidification process of the ingot, forming thermal cracks, which seriously affect the yield of aluminum alloy ingots.
[0003] D.H. · Deyang (patent application number CN1232664C) introduced a method for reducing ingot cracking in "Method for improving the surface properties of cast aluminum alloy and aluminum alloy produced by the method", which reduces ingot cracking by adding calcium, grain refiner and alkaline earth metal, transition metal and / or rare earth metal combination to the molten aluminum alloy substantially free of Be in the finished product. Lv Xinyu (patent application number CN101831567A) disclosed a method for preparing aluminum alloy ingots in "Method for preparing large-sized aluminum alloy ingots" to solve the problem that the existing method for preparing aluminum alloy ingots is prone to cracking when used to prepare large-sized aluminum alloy ingots. Wang Jiachun (patent application number CN101168186A) disclosed a DC casting equipment in "Continuous Lubricating Crystallizer for Semi-continuous Casting of Aluminum Alloys". Oil seeps into the graphite lining through the oil cavity to form a continuous oil film, which not only increases the lubrication effect of the graphite, but also plays a role in heat insulation and reducing the primary cooling of the ingot. Two independent water chambers can realize single or double water chambers to supply water at the same time, ensuring that thermal cracks do not occur in the early stage of aluminum alloy casting.
[0004] In the prior art, cast aluminum alloys are prone to thermal cracking. At the same time, it is difficult to coordinate and improve the mechanical strength and fracture properties of the product. In addition, the acid and alkali stability of the product is poor, which limits the use efficiency of the product. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a casting method for large-size aluminum alloys to solve the problems raised in the above background technology.
[0006] The present invention solves the technical problem by adopting the following technical solution:
[0007] The present invention provides a casting method for a large-size aluminum alloy, comprising the following steps:
[0008] Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment;
[0009] The specific steps of refining treatment are:
[0010] A refining agent is obtained by mixing 2-5 parts of potassium chloride, 1-3 parts of lithium chloride, 2-5 parts of yttrium oxide and 2-4 parts of a refinement modifier;
[0011] Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag;
[0012] Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 20-100 ppm of Be;
[0013] Step 3: Finally, the alloy body is obtained by filtering and casting;
[0014] Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed;
[0015] Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
[0016] Preferably, the nitrogen blowing treatment lasts for 10-15 minutes.
[0017] Preferably, the purity of the nitrogen is 90%.
[0018] Preferably, the preparation method of the refinement modifier is:
[0019] The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried;
[0020] 2-4 parts of nano-silica sol, 1-3 parts of urea, 2-5 parts of nano-silicon dioxide, and 2-5 parts of chitosan solution are fully mixed to obtain a modified solution;
[0021] 4-7 parts of dried graphene and 2-5 parts of modified liquid are mixed and ball-milled at a ball-milling speed of 450-500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a refined modifier.
[0022] Preferably, the mass fraction of the lanthanum nitrate solution is 2-5%; the mass fraction of the chitosan solution is 4-7%.
[0023] Preferably, the immersion power of the immersion treatment is 350-400W, and the immersion time is 20-30min.
[0024] Preferably, the preparation method of the ultrasonic liquid is:
[0025] The nano-bentonite is first heat treated at 310-330°C for 10-20 minutes, then cooled to 55°C at a rate of 2-5°C / min, and kept warm;
[0026] The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution;
[0027] 3-5 parts of nano-bentonite liquid, 1-3 parts of hydroxyapatite, 2-5 parts of silane coupling agent KH560, and 4-7 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
[0028] Preferably, the mass fraction of the sodium lignin sulfonate solution is 5-8%.
[0029] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic time is 20-30min.
[0030] Preferably, the specific operation steps of the thermal improvement treatment are:
[0031] First, the temperature of the first heat treatment is 220-230℃, and the treatment time is 10-20min; the temperature of the second heat treatment is 280-300℃, and the treatment time is 20-30min;
[0032] Finally, cool to 180°C at a rate of 1-3°C / min, keep warm for 10 minutes, and finally cool to room temperature at a rate of 2-5°C / min.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The casting method of the large-size aluminum alloy of the present invention adopts the method of completely melting the aluminum ingot and then refining treatment. The specific operation steps of the refining treatment are: using potassium chloride, lithium chloride, yttrium oxide and a refinement modifier to fully mix to obtain a refining agent for refining treatment, and then coordinating online degassing, casting molding, and ultrasonic modification treatment in a sufficient amount of ultrasonic liquid, and finally performing heat improvement treatment. The refining agent is used for refining treatment and coordinated with ultrasonic modification treatment in ultrasonic liquid and heat improvement treatment. It is difficult for the product to have thermal cracks. At the same time, the mechanical strength performance and fracture performance of the product are coordinated and improved, and the acid and alkali stability effect of the product is remarkable. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A casting method of a large-size aluminum alloy in this embodiment includes the following steps:
[0037] Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment;
[0038] The specific steps of refining treatment are:
[0039] A refining agent is obtained by mixing 2-5 parts of potassium chloride, 1-3 parts of lithium chloride, 2-5 parts of yttrium oxide and 2-4 parts of a refinement modifier;
[0040] Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag;
[0041] Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 20-100 ppm of Be;
[0042] Step 3: Finally, the alloy body is obtained by filtering and casting;
[0043] Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed;
[0044] Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
[0045] The nitrogen blowing treatment time in this embodiment is 10-15 minutes.
[0046] The purity of the nitrogen in this embodiment is 90%.
[0047] The preparation method of the refinement modifier of this embodiment is:
[0048] The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried;
[0049] 2-4 parts of nano-silica sol, 1-3 parts of urea, 2-5 parts of nano-silicon dioxide, and 2-5 parts of chitosan solution are fully mixed to obtain a modified solution;
[0050] 4-7 parts of dried graphene and 2-5 parts of modified liquid are mixed and ball-milled at a ball-milling speed of 450-500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a refined modifier.
[0051] The mass fraction of the lanthanum nitrate solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 4-7%.
[0052] The immersion power of the immersion treatment in this embodiment is 350-400W, and the immersion time is 20-30min.
[0053] The preparation method of the ultrasonic liquid of the present embodiment is:
[0054] The nano-bentonite is first heat treated at 310-330°C for 10-20 minutes, then cooled to 55°C at a rate of 2-5°C / min, and kept warm;
[0055] The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution;
[0056] 3-5 parts of nano-bentonite liquid, 1-3 parts of hydroxyapatite, 2-5 parts of silane coupling agent KH560, and 4-7 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
[0057] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5-8%.
[0058] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min.
[0059] The specific operation steps of the thermal improvement treatment of this embodiment are:
[0060] First, the temperature of the first heat treatment is 220-230℃, and the treatment time is 10-20min; the temperature of the second heat treatment is 280-300℃, and the treatment time is 20-30min;
[0061] Finally, cool to 180°C at a rate of 1-3°C / min, keep warm for 10 minutes, and finally cool to room temperature at a rate of 2-5°C / min.
[0062] Example 1.
[0063] A casting method of a large-size aluminum alloy in this embodiment includes the following steps:
[0064] Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment;
[0065] The specific steps of refining treatment are:
[0066] A refining agent is obtained by mixing 2 parts of potassium chloride, 1 part of lithium chloride, 2 parts of yttrium oxide and 2 parts of a refinement modifier;
[0067] Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag;
[0068] Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 20ppm of Be;
[0069] Step 3: Finally, the alloy body is obtained by filtering and casting;
[0070] Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed;
[0071] Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
[0072] The nitrogen blowing treatment time in this embodiment is 10 minutes.
[0073] The purity of the nitrogen in this embodiment is 90%.
[0074] The preparation method of the refinement modifier of this embodiment is:
[0075] The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried;
[0076] 2 parts of nano-silica sol, 1 part of urea, 2 parts of nano-silicon dioxide and 2 parts of chitosan solution are fully mixed to obtain a modified solution;
[0077] Four parts of dried graphene and two parts of modified liquid were mixed and ball-milled at a speed of 450 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water and dried to obtain a refined modifier.
[0078] The mass fraction of the lanthanum nitrate solution in this embodiment is 2%; the mass fraction of the chitosan solution is 4%.
[0079] The immersion power of the immersion treatment in this embodiment is 350 W, and the immersion time is 20 minutes.
[0080] The preparation method of the ultrasonic liquid of the present embodiment is:
[0081] The nano-bentonite was first heat treated at 310°C for 10 min, then cooled to 55°C at a rate of 2°C / min and kept warm;
[0082] The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution;
[0083] 3 parts of nano-bentonite liquid, 1 part of hydroxyapatite, 2 parts of silane coupling agent KH560, and 4 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
[0084] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%.
[0085] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350W, and the ultrasonic time is 20min.
[0086] The specific operation steps of the thermal improvement treatment of this embodiment are:
[0087] First, the primary heat treatment temperature is 220℃, and the treatment time is 10min; the secondary heat treatment temperature is 280℃, and the treatment time is 20min;
[0088] Finally, cool to 180°C at a rate of 1°C / min, keep warm for 10 min, and finally cool to room temperature at a rate of 2°C / min.
[0089] Example 2.
[0090] A casting method of a large-size aluminum alloy in this embodiment includes the following steps:
[0091] Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment;
[0092] The specific steps of refining treatment are:
[0093] A refining agent is obtained by mixing 5 parts of potassium chloride, 3 parts of lithium chloride, 5 parts of yttrium oxide and 4 parts of a refinement modifier;
[0094] Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag;
[0095] Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 100 ppm of Be;
[0096] Step 3: Finally, the alloy body is obtained by filtering and casting;
[0097] Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed;
[0098] Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
[0099] The nitrogen blowing treatment time in this embodiment is 15 minutes.
[0100] The purity of the nitrogen in this embodiment is 90%.
[0101] The preparation method of the refinement modifier of this embodiment is:
[0102] The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried;
[0103] 4 parts of nano-silica sol, 3 parts of urea, 5 parts of nano-silicon dioxide and 5 parts of chitosan solution are fully mixed to obtain a modified solution;
[0104] 7 parts of dried graphene and 5 parts of modified liquid were mixed and ball-milled at a speed of 500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water and dried to obtain a refined modifier.
[0105] The mass fraction of the lanthanum nitrate solution in this embodiment is 5%; the mass fraction of the chitosan solution is 7%.
[0106] The immersion power of the immersion treatment in this embodiment is 400 W, and the immersion time is 30 minutes.
[0107] The preparation method of the ultrasonic liquid of the present embodiment is:
[0108] The nano-bentonite was first heat treated at 330°C for 20 min, then cooled to 55°C at a rate of 5°C / min and kept warm;
[0109] The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution;
[0110] 5 parts of nano-bentonite liquid, 3 parts of hydroxyapatite, 5 parts of silane coupling agent KH560, and 7 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
[0111] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 8%.
[0112] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.
[0113] The specific operation steps of the thermal improvement treatment of this embodiment are:
[0114] First, the primary heat treatment temperature is 230℃, and the treatment time is 20min; the secondary heat treatment temperature is 300℃, and the treatment time is 30min;
[0115] Finally, cool to 180°C at a rate of 3°C / min, keep warm for 10 min, and finally cool to room temperature at a rate of 5°C / min.
[0116] Example 3.
[0117] A casting method of a large-size aluminum alloy in this embodiment includes the following steps:
[0118] Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment;
[0119] The specific steps of refining treatment are:
[0120] A refining agent is obtained by mixing 3.5 parts of potassium chloride, 2 parts of lithium chloride, 3.5 parts of yttrium oxide and 3 parts of a refinement modifier;
[0121] Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag;
[0122] Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 60ppm of Be;
[0123] Step 3: Finally, the alloy body is obtained by filtering and casting;
[0124] Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed;
[0125] Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
[0126] The nitrogen blowing treatment time in this embodiment is 12 minutes.
[0127] The purity of the nitrogen in this embodiment is 90%.
[0128] The preparation method of the refinement modifier of this embodiment is:
[0129] The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried;
[0130] 3 parts of nano-silica sol, 2 parts of urea, 3.5 parts of nano-silicon dioxide, and 3.5 parts of chitosan solution are fully mixed to obtain a modified solution;
[0131] 5.5 parts of dried graphene and 3.5 parts of modified liquid were mixed and ball-milled at a ball-milling speed of 475 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water and dried to obtain a refined modifier.
[0132] The mass fraction of the lanthanum nitrate solution in this embodiment is 3.5%; the mass fraction of the chitosan solution is 5%.
[0133] The immersion power of the immersion treatment in this embodiment is 375 W, and the immersion time is 25 min.
[0134] The preparation method of the ultrasonic liquid of the present embodiment is:
[0135] The nano-bentonite was first heat treated at 320°C for 15 min, then cooled to 55°C at a rate of 3.5°C / min and kept warm;
[0136] The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution;
[0137] 4 parts of nano-bentonite liquid, 2 parts of hydroxyapatite, 3.5 parts of silane coupling agent KH560, and 5.5 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
[0138] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 6.5%.
[0139] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 375W, and the ultrasonic time is 25min.
[0140] The specific operation steps of the thermal improvement treatment of this embodiment are:
[0141] First, the primary heat treatment temperature is 225℃, and the treatment time is 15min; the secondary heat treatment temperature is 290℃, and the treatment time is 25min;
[0142] Finally, cool to 180°C at a rate of 2°C / min, keep warm for 10 min, and finally cool to room temperature at a rate of 3.5°C / min.
[0143] Example 4.
[0144] A casting method of a large-size aluminum alloy in this embodiment includes the following steps:
[0145] Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment;
[0146] The specific steps of refining treatment are:
[0147] A refining agent is obtained by mixing 3 parts of potassium chloride, 2 parts of lithium chloride, 3 parts of yttrium oxide and 3 parts of a refinement modifier;
[0148] Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag;
[0149] Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 50ppm of Be;
[0150] Step 3: Finally, the alloy body is obtained by filtering and casting;
[0151] Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed;
[0152] Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
[0153] The nitrogen blowing treatment time in this embodiment is 12 minutes.
[0154] The purity of the nitrogen in this embodiment is 90%.
[0155] The preparation method of the refinement modifier of this embodiment is:
[0156] The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried;
[0157] 2 parts of nano-silica sol, 2 parts of urea, 4 parts of nano-silicon dioxide, and 3 parts of chitosan solution are fully mixed to obtain a modified solution;
[0158] 5 parts of dried graphene and 3 parts of modified liquid were mixed and ball-milled at a speed of 460 r / min for 2 h. After the ball-milling was completed, the mixture was washed with water and dried to obtain a refined modifier.
[0159] The mass fraction of the lanthanum nitrate solution in this embodiment is 3%; the mass fraction of the chitosan solution is 4%.
[0160] The immersion power of the immersion treatment in this embodiment is 390 W, and the immersion time is 24 minutes.
[0161] The preparation method of the ultrasonic liquid of the present embodiment is:
[0162] The nano-bentonite was first heat treated at 312°C for 14 min, then cooled to 55°C at a rate of 3°C / min and kept warm;
[0163] The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution;
[0164] 4 parts of nano-bentonite liquid, 2 parts of hydroxyapatite, 3 parts of silane coupling agent KH560, and 6 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
[0165] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 7%.
[0166] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 380W, and the ultrasonic time is 28min.
[0167] The specific operation steps of the thermal improvement treatment of this embodiment are:
[0168] First, the primary heat treatment temperature is 222℃, and the treatment time is 18min; the secondary heat treatment temperature is 285℃, and the treatment time is 27min;
[0169] Finally, cool to 180°C at a rate of 2°C / min, keep warm for 10 min, and finally cool to room temperature at a rate of 4°C / min.
[0170] Comparative Example 1.
[0171] The difference from Example 3 is that no refining treatment was used.
[0172] Comparative Example 2.
[0173] The difference from Example 3 is that no refining modifier is added during the refining process.
[0174] Comparative Example 3.
[0175] The difference from Example 3 is that no modifying liquid treatment is used in the preparation of the refined modifier.
[0176] Comparative Example 4.
[0177] The difference from Example 3 is that no urea or nano-silicon dioxide is added to the modified liquid.
[0178] Comparative Example 5.
[0179] The difference from Example 3 is that ultrasonic liquid treatment is not used.
[0180] Comparative Example 6.
[0181] The difference from Example 3 is that no nano-bentonite liquid is added to the ultrasonic liquid.
[0182] Comparative Example 7.
[0183] The difference from Example 3 is that hydroxyapatite and silane coupling agent KH560 are not added to the ultrasonic liquid.
[0184] Comparative Example 8.
[0185] The difference from Example 3 is that no thermal improvement treatment is used.
[0186] The products of Examples 1-4 and Comparative Examples 1-8 were subjected to conventional performance tests, and the products were placed in 2% hydrochloric acid mist for 12 hours, and then placed in 2% sodium hydroxide alkaline mist for 12 hours to test the acid and alkali stability of the products;
[0187]
[0188]
[0189] It can be seen from Comparative Examples 1-8 and Examples 1-4 that the product of Example 3 has excellent yield strength and elongation, and the two properties can be improved in a coordinated manner, and the acid and alkali resistance stability of the product is significant;
[0190] If the product is not treated with refining, ultrasonic liquid treatment or heat improvement, the performance of the product will deteriorate significantly. The synergistic effect of the three treatments will be the most significant.
[0191] No refinement modifier was added in the refining treatment, no modification liquid treatment was used in the preparation of the refinement modifier, no urea and nano-silicon dioxide were added to the modification liquid, no nano-bentonite liquid was added to the ultrasonic liquid, no hydroxyapatite and silane coupling agent KH560 were added to the ultrasonic liquid, and the performance of the products showed a trend of deterioration. Only the product raw material obtained by the method of the present invention has the most significant performance effect of the product, and the effects of other methods are not as obvious as those of the present invention.
[0192] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0193] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A casting method for large-size aluminum alloy, characterized in that: The following steps are involved: Step 1: Melt the aluminum alloy ingot completely and then perform refining treatment; The specific steps of refining treatment are: A refining agent is obtained by mixing 2-5 parts of potassium chloride, 1-3 parts of lithium chloride, 2-5 parts of yttrium oxide and 2-4 parts of a refinement modifier; Add the refining agent into the completely smelted aluminum alloy liquid and stir it thoroughly, use nitrogen blowing treatment, and then remove the slag; Step 2: After online degassing, AlBe5 master alloy is added to the aluminum alloy melt in the online degassing box during online degassing, so that the aluminum alloy melt contains 20-100 ppm of Be; Step 3: Finally, the alloy body is obtained by filtering and casting; Step 4: subjecting the alloy body to ultrasonic modification in a sufficient amount of ultrasonic liquid, and drying after the ultrasonic treatment is completed; Step 5: Finally, the large-size aluminum alloy of the present invention can be obtained after the reheating improvement treatment is completed.
2. A casting method for a large-size aluminum alloy according to claim 1, characterized in that: The nitrogen blowing treatment lasts for 10-15 minutes.
3. The casting method of a large-size aluminum alloy according to claim 1, characterized in that: The purity of the nitrogen is 90%.
4. The casting method of a large-size aluminum alloy according to claim 1, characterized in that: The preparation method of the refinement modifier is: The graphene is first immersed in a sufficient amount of lanthanum nitrate solution, and after the immersion is completed, the graphene is filtered and dried; 2-4 parts of nano-silica sol, 1-3 parts of urea, 2-5 parts of nano-silicon dioxide, and 2-5 parts of chitosan solution are fully mixed to obtain a modified solution; 4-7 parts of dried graphene and 2-5 parts of modified liquid are mixed and ball-milled at a ball-milling speed of 450-500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a refined modifier.
5. A casting method for a large-size aluminum alloy according to claim 4, characterized in that: The mass fraction of the lanthanum nitrate solution is 2-5%; the mass fraction of the chitosan solution is 4-7%.
6. A casting method for a large-size aluminum alloy according to claim 4, characterized in that: The immersion power of the immersion treatment is 350-400W, and the immersion time is 20-30min.
7. A casting method for a large-size aluminum alloy according to claim 1, characterized in that: The preparation method of the ultrasonic liquid is: The nano-bentonite is first heat treated at 310-330°C for 10-20 minutes, then cooled to 55°C at a rate of 2-5°C / min, and kept warm; The heat-insulated nano-bentonite is first mixed with a sufficient amount of sodium lignin sulfonate solution to obtain a nano-bentonite solution; 3-5 parts of nano-bentonite liquid, 1-3 parts of hydroxyapatite, 2-5 parts of silane coupling agent KH560, and 4-7 parts of sodium carboxymethyl cellulose are fully blended to obtain an ultrasonic liquid.
8. A casting method for a large-size aluminum alloy according to claim 7, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 5-8%.
9. A casting method for a large-size aluminum alloy according to claim 1, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic time is 20-30min.
10. A casting method for a large-size aluminum alloy according to claim 1, characterized in that: The specific operation steps of the thermal improvement treatment are: First, the temperature of the first heat treatment is 220-230℃, and the treatment time is 10-20min; the temperature of the second heat treatment is 280-300℃, and the treatment time is 20-30min; Finally, cool to 180°C at a rate of 1-3°C / min, keep warm for 10 minutes, and finally cool to room temperature at a rate of 2-5°C / min.
Citation Information
Patent Citations
Continuous lubricating crystallizer for aluminum alloy semi-continuous casting
CN101168186A
Preparation method of large-size aluminum alloy ingot
CN101831567A
Method for improving aluminium alloy surface performance and aluminium alloy produced thereby
CN1232664C